2000
DOI: 10.1002/chin.200016159
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structural Characterization of Boron Subphthalocyaninates.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In our hands, the synthesis of Br-BsubPc as described by Potz et al 4 was found to be successful after some adaptations. The process is similar to that used for Cl-BsubPc in that it starts by dissolving phthalonitrile in solvent and adding a boron trihalide (in this case neat BBr 3 , Scheme 1).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In our hands, the synthesis of Br-BsubPc as described by Potz et al 4 was found to be successful after some adaptations. The process is similar to that used for Cl-BsubPc in that it starts by dissolving phthalonitrile in solvent and adding a boron trihalide (in this case neat BBr 3 , Scheme 1).…”
Section: Resultsmentioning
confidence: 62%
“…The saturated solution was then sampled, passed through a GS-Tek PTFE 13 mm 0.22 μm syringe filter, and serially diluted until the absorbance fell within the linear range of the spectrometer. The absorption spectrum 4 as follows: In a 100 mL three-neck round bottomed flask, equipped with a magnetic stir-bar, a gas inlet, a condenser, and two rubber sleeve stoppers, phthalonitrile (4.0 g, 0.0312 mol) was dissolved in a 3:1 mixture of toluene−bromobenzene (50 mL). The vessel was kept under an inert atmosphere of argon, and a syringe and needle were used to slowly add boron tribromide (0.96 mL, 0.010 mol) to the solution.…”
Section: Introductionmentioning
confidence: 99%
“…3-Methylphenoxy-Boron Subphthalocyanine (3-MePhO-BsubPc, 8). Br-BsubPc was prepared based on the method previously reported 44 by modifying a published procedure by Potz et al 32 A similar procedure to the one previously described by Paton et al was followed. 17 Br-BsubPc was used as a starting material instead of Cl-BsubPc to decrease the reaction time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is in fact known that the axial boron-chloride bond is labile already in the presence of moderate nucleophiles in solution. 52 Also, dechlorination is a known process for instance in the case of iron octaethylporphyrin chloride (FeCl-OEP) on Cu(111) 45 and Au(III)-tetraphenylporphyrin chloride ([Au III TPP] + Cl – ) on Au (111). 44 Note that at least in the case of FeCl-OEP on Cu(111) chlorine adatoms were not clearly visible either.…”
Section: Resultsmentioning
confidence: 99%